THE EFFECTS OF MODEL PROJECT-BASED LEARNING APPROACH ON STEM (SCIENCE, TECHNOLOGY, ENGINEERING, MATHEMATIC) ON SCIENCE LEARNING TO JUNIOR HIGH SCHOOL STUDENT’S CRITICAL THINKING SKILLS AND COOPERATIVE SKILLS - Riyani Septi Indriyana; Susilowati Susilowati (Journal of Science Education Research, 2020)
The research aimed to (1) analyzes the effects of model project-based learning approach on  STEM (science, technology, engineering, mathematic) on science learning to junior high school student’s critical thinking skills and cooperative skills, and (2) analyze how the effects of model project-based learning approach on STEM (science, technology, engineering, mathematic) on science learning to junior high school student’s critical thinking skills and cooperative skills. The research was quasi-experimental with a non-equivalent control group design. The population was eighth-grade students of SMP Negeri 1 Berbah. The sample of the study was selected with cluster random sampling techniques and obtained grade-VIII B as an experimental class and grade-VIII C as a control class. Learning in the experimental class with a project-based learning model was STEM-oriented and the control class used a scientific approach. The data were pretest and posttest of critical thinking and observation sheets of cooperation. The analysis used the normality test, homogeneity test, MANOVA  test, and effect size. The results showed that (1) there was an effect of project based learning model on STEM approach on critical thinking skills and cooperative skills of students of SMP Negeri 1 Berbah, (2) the effect of science learning project based learning model on STEM approach on critical thinking and collaborative skill was on medium category.